The expansion of supermarkets and the establishment of delivery systems and intermediaries for fresh fruit and vegetables in the Global South – the case of Kenya and Tanzania - Sonntag, Christian; Kulke, Elmar (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
In the last three decades, supermarket chains from the countries of the Global North expanded in the Global South. The regions of interest were, in particular, those countries in which new market potentials resulted from economic development. There is also the trend that domestic supermarket chains are developing in the countries of the Global South. A number of studies in the Global South analyzes the impact on agricultural producers by incorporating them into delivery systems to supermarkets. However, little evidence exists yet on how the delivery systems are organized by intermediaries between agricultural producers and the supermarket chains in the Global South. Especially for fresh produce (vegetables, fruit) special challenges occur., e.g. concerning infrastructures This article will examine the relationship between the spatial and temporal expansion of supermarket chains and the establishment of delivery systems/intermediaries using the example of fresh produce in the countries of Kenya and Tanzania.